To be or not: Exploring the sense of meaninglessness among Chinese undergraduates - Wang, Heyuan; Qiu, Qingquan; Zhu, Jiayao; Ge, Qingqing; Smith, Clayton; Ding, Wenqian; Donghai, Gan (Journal of International Students, 2025)
In this paper, we investigate the pervasive sense of meaninglessness among Chinese undergraduates, examining the multifaceted influences of educational models, social media pressures, peer competition, and family dynamics. Through qualitative interviews, the research reveals how these factors shape students’ well-being and academic experiences, highlighting the need for comprehensive support systems to address existential crises. The findings reveal the complex interplay between external pressures and internal values, emphasizing the importance of integrating practical experiences, enhancing digital literacy, and promoting student-centered learning to foster a more meaningful university experience. This study contributes novel insights to the discourse on student mental health and academic success in higher education.